2018
DOI: 10.1111/jam.13760
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake rate in alginate producer (algU+) and nonproducer (algU−) strains ofAzotobacter vinelandiiunder nitrogen-fixation conditions

Abstract: This study highlights the role of AlgU to control respiration of A. vinelandii when exposed to diazotrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Recent studies suggest involvement of EPS in protecting heterotrophic nitrogen fixers of the species Azotobacter vinelandii (12, 51, 52). This has been supported by a laboratory study where respiration decreases with EPS production (53). Trichodesmium produces EPS especially under nutrient-limited conditions (5456).…”
Section: Discussionmentioning
confidence: 66%
“…Recent studies suggest involvement of EPS in protecting heterotrophic nitrogen fixers of the species Azotobacter vinelandii (12, 51, 52). This has been supported by a laboratory study where respiration decreases with EPS production (53). Trichodesmium produces EPS especially under nutrient-limited conditions (5456).…”
Section: Discussionmentioning
confidence: 66%
“…In addition, in the vegetative stage, alginate may serve as a diffusion barrier for oxygen to protect the nitrification system of the bacteria. 3 Alginate forms ionotropic gels with divalent cations such as calcium where the presence of G-blocks is the main structural feature contributing to gel formation. The mechanism behind gel formation is most easily visualized by analogy with an egg seven epimerase genes (algE1−algE7), all of which have been cloned and expressed in Escerichia coli.…”
Section: ■ Introductionmentioning
confidence: 99%
“…alginate is essential for the cyst formation, where an alginate gel forms the protective walls on metabolic dormant cysts. In addition, in the vegetative stage, alginate may serve as a diffusion barrier for oxygen to protect the nitrification system of the bacteria …”
Section: Introductionmentioning
confidence: 99%
“…From the significance of differences at p < 0.05, it can be concluded that bacteria grown in conditions with high aeration and low sucrose concentration in cultural medium do not have sufficient carbon source for constant exponential growth, and, therefore, after 48 h they enter the stationary phase (C−/O+). It can be assumed that the role of carbon as the main source for bacteria growth increases due to high agitation rate (O+) [ 46 ]. So, Barrera and his colleagues demonstrated that upon elevation of the aeration level, A. vinelandii begins to consume carbon as much as possible, where 25% of it is spent on the biosynthesis of alginate [ 47 ].…”
Section: Resultsmentioning
confidence: 99%